2023
DOI: 10.3390/lubricants11010025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nozzle Layouts on the Heat-Flow Coupled Characteristics for Oil-Jet Lubricated Spur Gears

Abstract: Aiming to explore the influence of nozzle layouts on the lubrication and cooling performance of spur gears under oil jet lubrication conditions, this paper introduces a heat-flow coupled analysis method to predict the temperature field of the tooth surface with different nozzle layouts. Firstly, the friction heat formulas integrating the coefficient of friction and average contact stress are presented for calculating heat generation. We also present the impingement depth model, which considers the nozzle orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…[5] proposed a model to predict the overall temperature of a mechanical transmission; (ii) Long [6] simulated the temperature of gear teeth at high speeds, taking into account the effects of gear geometry, rotational speed, and lubrication conditions; (iii) Townsend et al [7] developed a computer program for predicting gear-tooth temperatures and the importance of oil jet cooling in preventing scoring, with the need for an experimental determination of heat-transfer coefficients. In addition to the above-mentioned studies, the works of Xing C. [8], G. Niemann [9], Peng Jie [10], and Duan Yang [11] showed that for gears operating under high speeds, a pressurized oil jet is required to provide adequate cooling and prevent gear failure caused by high bulk temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[5] proposed a model to predict the overall temperature of a mechanical transmission; (ii) Long [6] simulated the temperature of gear teeth at high speeds, taking into account the effects of gear geometry, rotational speed, and lubrication conditions; (iii) Townsend et al [7] developed a computer program for predicting gear-tooth temperatures and the importance of oil jet cooling in preventing scoring, with the need for an experimental determination of heat-transfer coefficients. In addition to the above-mentioned studies, the works of Xing C. [8], G. Niemann [9], Peng Jie [10], and Duan Yang [11] showed that for gears operating under high speeds, a pressurized oil jet is required to provide adequate cooling and prevent gear failure caused by high bulk temperatures.…”
Section: Introductionmentioning
confidence: 99%